Self‐Powered and Broadband Photodetectors with GaN: Layered rGO Hybrid Heterojunction. Issue 20 (20th August 2019) - Sarkar, Krishnendu; Hossain, Mozakkar; Devi, Pooja; Rao, K. D. M.; Kumar, Praveen
Abstract: The development of self‐powered and broadband (NIR–Vis–UV) photodetectors with high responsivity is essential for energy efficient futuristic optoelectronic devices. A simple approach is reported to formulate inorganic–organic (GaN/rGO: Ag NP) hybrid p–n heterojunction photodetectors clasping with transparent Au nanowire network as the top electrode. The heterojunction demonstrates excellent rectification ratio of 10 5 and broadband photoresponse due to GaN in ultraviolet (UV) region and silver‐loaded reduced graphene oxide (rGO: Ag NP) in visible to infrared region. Further, the reducing effect of Ag nanoparticles (Ag NPs) to GO along with its localized surface plasmon resonance is utilized to enhance the response in near infrared (NIR) and the visible region in the presented device structure. Transparent Au nanowire network works as an efficient charge collector ensuing high responsivity and fast switching characteristics. The heterojunction exhibits superior photoresponse with high on/off ratio (10 4 ), responsivity (0.266 A W ‐1 ), and detectivity of (2.62 × 10 11 ), under the illumination of 360 nm light. Due to the high built‐in‐potential difference at the heterojunctions, self‐powered operation is demonstrated under entire excitation wavelength (360–980 nm) range, which holds great futuristic promises for cost‐effective, stable, and efficient energy conserving electronics. Abstract : An optimal design using a simple approach to formulate inorganic–organic (GaN/rGO: Ag NP) hybrid p–n heterojunction photodetectors clasped with transparent Au metal nanowire network as the top electrode is presented. The combination of GaN responsive in UV region and optically transparent silver doped reduced graphene oxide (rGO: Ag NP) responsive in the visible to NIR region provides broadband detection.